The Hitchhiker’s guide to the rhinencephalon - Silveira-Moriyama, Laura; Glass, Philip; Rajan, Suraj; Carvalho, Rafael; Reis, Fabiano; Penatti, Carlos A. A.; Muio, Valeria (Arquivos de Neuro-Psiquiatria, 2016)
Pathology of the rhinencephalon has been a subject of interest in the fields of neurodegenerative diseases, trauma, epilepsy and other neurological conditions. Most of what is known about the human rhinencephalon comes from comparative anatomy studies in other mammals and histological studies in primates. Functional imaging studies can provide new and important insight into the function of the rhinencephalon in humans but have limited spatial resolution, limiting its contribution to the study of the anatomy of the human rhinencephalon. In this study we aim to provide a brief and objective review of the anatomy of this important and often overlooked area of the nervous system.
Keywords: olfactory cortex; anatomy; neuroanatomy